The Analysis and Optimization of Broadband Fiber Optical Parametric Amplifiers Pumped by Chirped Pulses - Stefano Taccheo (IEEE Journal of Selected Topics in Quantum Electronics, 2019)
The broadband gain properties of fiber optical parametric amplifiers pumped both by one and two chirped pump pulses are investigated for the amplification of ultrashort pulses, analytically with the gain spectrum calculated in both the anti-Stokes’ and Stokes’ side. The influence of chirp rate and time delay on the gain spectrum of fiber-based optical parametric chirped pulse amplification is mainly explored. It is shown that the chirp rate and time delay distinctly affect the second order dispersion and phase mismatching, leading to the gain variation; the two pump scheme provides broader gain bandwidth, especially under the condition of the two chirp rate with low absolute value; and a genetic algorithm is employed to optimize the gain characteristics for realizing a flatter and wider, high gain that is useful for the ultrashort pulse system.